Impact of a Comprehensive Antimicrobial Stewardship Program on Institutional Burden of Antimicrobial Resistance: A 14-Year Controlled Interrupted Time-series Study. (9th December 2019) - Peragine, Christine; Walker, Sandra A N; Simor, Andrew; Walker, Scott E; Kiss, Alexander; Leis, Jerome A
Abstract: Background: Antimicrobial resistance (AMR) constitutes an international public health threat widely believed to result from excessive antimicrobial use (AMU). Numerous authorities have recommended antimicrobial stewardship programs (ASPs) to curb the selection of AMR, but there is a lack of data confirming this benefit. Methods: A controlled interrupted time-series study spanning 14 years was performed to assess impact of a comprehensive hospital-based ASP that included pharmacist-led audit and feedback on institutional AMR. Patient-level microbiologic and AMU data were obtained from October 2002 to September 2016. Poisson regression models were used to identify changes in the incidence and trend of hospital-acquired (HA) antibiotic-resistant organisms (AROs) and multidrug-resistant organisms (MDROs). Changes in community-acquired (CA)–ARO, CA-MDRO, and inpatient AMU were assessed as controls and process outcomes. Results: Statistically significant shifts in AMU, HA-ARO, and HA-MDRO trends coinciding with ASP implementation were observed, corresponding with a 9% reduction in HA-ARO burden (incidence rate ratio [IRR], 0.91 [95% confidence interval CI, .83–.99]; P = .03) and a 13% reduction in HA-MDRO burden (IRR, 0.87 [95% CI, .73–1.04]; P = .13) in the intervention period. In contrast, CA-ARO and CA-MDRO incidence continued to rise, with 40% (IRR, 1.40 [95% CI, 1.28–1.54]; P < .0001) and 68% (IRR, 1.68 [95% CI, 1.57–1.82]; P < .0001) increases in burden found, respectively. Conclusions: Implementation of a comprehensive ASP resulting in reduced AMU was associated with a significant reduction in institutional AMR, even though community AMR increased during the same period. These results confirm that ASPs play an important role in the fight against AMR. Abstract : Implementation of a comprehensive antimicrobial stewardship program (ASP) significantly reduced nosocomial antimicrobial resistance (AMR) even though community AMR (control) increased during the same period. This study provides evidence that ASPs play an important role in the fight against AMR.